Augmenting effect of infill density and annealing on mechanical properties of PETG and CFPETG composites fabricated by FDM. (2021) - Sathish Kumar, K.; Soundararajan, R.; Shanthosh, G.; Saravanakumar, P.; Ratteesh, M.
Abstract: Recently, Polyethylene Terephthalate Glycol (PETG) and Carbon Fiber reinforced Polyethylene Terephthalate Glycol (CFPETG) composites have become the excellent material choice for automotive and other industrial applications in desktop-based Fused Deposition Modeling (FDM) technique. In FDM technique the process parameters affect the dimensional stability, quality, functionality and properties of the printed specimens. The present article discusses the effects of infill density of FDM on mechanical properties of samples printed with PETG and CFPETG material. The test samples were printed through FDM by layers of extruded beads by varying significant parameter of infill density like 25%, 50%, 75%and 100% respectively and the remaining parameters were kept constant in optimal value. The infill density followed by annealing determines the overall mechanical performance. In accordance with the former mechanical properties like hardness, tensile strength, impact strength and flexural strength enhanced as the increased 100% infill density in PETG and CFPETG samples. The interlayer diffusion bonding was increased and enhanced the mechanical properties via suitable post-processing method of annealing which was a secondary focus of this study to compare with as-printed sample. It is evident that the responses in this finding provide a beneficial guideline for producing functional parts by using CFPETG and considering 100% infill density with annealing which was almost significant one for automobile and aeronautical structural metallic components replacement in future.